Sociodemographic Disparities in the Prevalence of Metabolic Syndrome in Rural South Africa: An Analysis of Gender, Age, and Marital, Employment, and Educational Status - Dimakatso Given Mashala; Cairo Bruce Ntimana; Kagiso Peace Seakamela; Reneilwe Given Mashaba; Eric Maimela (Obesities)
Sociodemographic factors affect how metabolic syndrome (MetS) manifests and progresses. This study aimed to investigate the prevalence between MetS and sociodemographic factors among adult participants in the Dikgale HDSS. This was a comprehensive retrospective study where the records of 575 participants were meticulously evaluated. MetS was defined using a joint interim statement (JIS). The data were analyzed using the Statistical Package for SPSS, version 25. A chi-square test was used to compare proportions between groups, with Cramer’s V used to assess the strength of association. Logistic regression was used to determine the association between MetS and sociodemographic profiles. A p-value of less than 0.05 was considered statistically significant. The prevalence of MetS was 28.2% (females 33.3% vs. males 15.6%, p ≤ 0.001). In addition, logistic regression showed males to have lower odds of MetS as compared to females (OR = 0.36, 95% CI: 0.2–0.6, and AOR = 0.4, 95% CI: 0.2–0.6). The 55–60 age group had the highest proportion of affected individuals, and MetS was also more common among individuals with low educational attainment. In addition, on regression, the same association was observed. This study found sociodemographic disparities in MetS among rural adults, especially females, who had an increased risk of MetS, and participants with low educational attainment.